PENGARUH OPINI AUDIT BPK, PENDAPATAN ASLI DAERAH (PAD) DAN INTERGOVERNMENTAL REVENUE TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DI JAWA TIMUR TAHUN 2017-2019 - Andre Bayu Pratama; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The financial performance of local governments is a measure of the success of local governments in managing resources originating from their regions or the central government. Management independently and jointly provide excellent service to society. The purpose of this study is to find out the effect of the Audit Opinion of BPK, Local Revenue (PAD) and Intergovernmental Revenue on the Financial Performance of Local Governments in East Java in 2017-2019, either simultaneously or partially. The research used the associative method with a quantitative approach. The data used secondary data with a time series of three years. The population used the Audit Result Report (LHP) obtained from the Audit Board of Indonesia. The sampling technique used purposive sampling and obtained 29 districts in East Java and 87 LHP for three years. Data analysis used multiple linear regression analysis. Meanwhile, the data processing used IBM Statistical Package for the Social Sciences type 22. The results of this study explain that the Audit Opinion of BPK has no effect on the Financial Performance of Local Governments. The PAD variable has a significant negative effect on the Financial Performance of Local Governments and the Intergovernmental Income variable has a significant negative effect on the Financial Performance of Local Governments.  Keyword: Audit Opinion BPK, Local Revenue, Intergovernmental Revenue, Financial Performance of Local Government